The Application of Developmental Care by Providing Snuggle Up positioning in BBLR-Premature Infants - Reni Ilmiasih; Muhammad Fajar Ratanca Duri (STIKes Patria Husada Blitar, 2024)
One of the main causes of death in neonates is low birth weight (LBW), which is the condition of babies with birth weight < 2500 grams from gestational age < 37 weeks. Problems that often occur in LBW are thermoregulation disorders, respiratory disorders, nutritional disorders and others. This case study was conducted to describe developmental care interventions on the comfort level of premature LBW infants. This study used a case study design with an evidence-based practice implementation approach that focuses on interventional nursing. The study was conducted in the NICU of RSU UMM on 24-26 October 2023. The participants in this study were Baby Mrs. P aged 0 years, 0 month, 0 days, male, with LBW-Premature. Measurement of comfort level using NIPS and Comfort-B Scale through physical examination and observation every 7 hours for 3 days. Patient observation showed that there was a decrease in pain level and an increase in the baby's comfort level every day. This could be seen from the NIPS score on the first day of treatment from 7 points (severe pain) to 0 points (no pain) on the third day, and the Comfort-B score from 25 points (moderate comfort) to 8 points (high comfort). The application of Snuggle up Position can effectively reduce the level of pain scale and increase the comfort scale in LBW-premature infants in the hospital